Elaboración de material de enseñanza impreso para fortalecer procesos de lectura con sentido y significado (2017)
In the pedagogical practices of language carried out within the framework of the proposal of the Degree program in Spanish and English Language of the Antonio Nariño University, the privilege of decoding processes in the teaching and learning of unknown reading was demonstrated.